(untitled) (Fiep Bulletin - online, 2014)
So that the Physical Education reaches its maxim expression inside of the school’s curriculum, it should provide to the individual the largest number of gratifying educational experiences around the idea of making possible a self-awareness and corporal acceptance, with the development of the taste for the Physical Education classes. The objective of that project is addressed for the socializing of Tennis, through its inclusion in schools using the methodology of mini-tennis, and several are the countries that already introduced the modality referred with great success, standing out Spain, inside of the Catalan Federation of Tennis. In Brazil several conventional projects of implantation of tennis exist at the schools, but the high price of the materials used and the lack of the Physical Education teachers’ preparation that work at the schools, have been the largest barrier to be conquered. The Project Tênis Júnior in the Schools is a partnership among the Nucleus of Studies in Tennis (NETEC) of the Federal University of Santa Catarina (UFSC), with the company Guarani Industry and Trade. The material developed by the Guarani (net, rackets and balls), of accessible cost and appropriate to the practice, possessing dimensions that respect the characteristics of the mini-tennis, conjugated with the didactic course for the physical education teachers and plus the didactic-pedagogic material of this project, besides the coordination of the project during the whole first year, are important factors for the success of the implantation of tennis in the schools in Brazil. Now the project is being developed at schools of the municipal, state and private nets of Santa Catarina, where approximately 130 thousand students are participating in the project through the Physical Education classes, and more than 600 teachers already participated of the formation course to work with tennis in the schools, including an amount of 200 schools.